Thijssen, zittend, rechts, met het personeel van school 104 in de 2de Boerhavestraat. Origineel bij mevr. G. Thijssen, Amsterdam (1919)
Thijssen, zittend, rechts, met het personeel van school 104 in de 2de Boerhavestraat. Origineel bij mevr. G. Thijssen, Amsterdam.